SISTEM INFORMASI MANAJEMEN NEGERI TAWIRI BERBBASIS WEB - Ari Permana L; Victor Febian Puturuhu, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
This research is motivated by service activities for the community where the current condition that occurs in the service is when carrying out data collection The residents of Tawiri country have several obstacles that are often faced, such as the process Population data recording is still manual or paper-based, so this occurs accumulation of paper in therchive room of the State Government Office. Previous research used as a reference is Riady, I., & Hasugian,. (2020) Information Systems Community Services at the Tanimulya Village Office Theories used in This research is carried out by Prasetiyo and R.P Daniawaty, Indonesian Computer University In 2020, Definition of application according to Eka Noviansyah (2008:4) Data Flow Diagram According to (H.M. Jogiyanto, 1989:700). The methodology that will be used in this research is Communication which includes literature studies, by collecting data, Observations, interviews and field reviews and documentation. Next stage namely analysis with the aim of studying the flow in the service stages, after that design is carried out to design the new system that will be created, entering the stage next is Construction to create a system or application according to the design which has been made. The next stage is testing the program that has been created with the aim of testing whether there are still problems in testing If there are still problems, they will be repaired immediately, the last stage is the implementation stage, namely running the application so that it can be used by the people of Tawiri Country